The prescription of direct oral anticoagulants in the elderly: An observational study of 19 798 Ambulatory subjects. Issue 1 (24th October 2019) - Barben, Jérémy; Menu, Didier; Rosay, Clémentine; Vovelle, Jérémie; Mihai, Anca‐Maria; Nuss, Valentine; d'Athis, Philippe; Putot, Alain; Manckoundia, Patrick
Summary: Objective: Direct oral anticoagulants (DOACs) are increasingly prescribed to elderly people, but the epidemiologic data for this population remains scarce. We compared the elderly population taking DOACs and those not taking DOACs (noDOAC). Method: We included individuals over 75 years old, affiliated to Mutualité Sociale Agricole of Burgundy (a French regional health insurance agency), who had been refunded for a prescribed DOAC between 1st and 30th September 2017. The DAOC group (DAOCG) and noDOAC group (noDOACG) were compared in terms of demographic conditions, registered chronic diseases (RCD), and number and types of prescribed drugs. In the DOACG, we compared the type of prescribing physician and laboratory monitoring for novel prescriptions (initial) and prescription refills (≥ 3 months). Results: Of the 19 798 included patients, 1518 (7.7%) were prescribed DAOCs and 18 280 (92.3%) were not. Mean and median age was 85 years in the 2 groups (DOACG and noDOACG). In the DOACG, there were more men (50% vs 40.2%), more RCD (88.9% vs 68.7%) and more drugs per prescription (6 ± 2.8 vs 5 ± 2.9) (All P < .01). The DOACG also took more antihypertensive drugs. The most commonly prescribed DOACs were apixaban (42.9%) followed by rivaroxaban (38.4%) and dabigatran (18.6%). Complete blood count, serum creatinine and coagulation function tests were requested for 69.4%, 75% and 22.2%, respectively, of patients prescribed DAOCs. Conclusions: The DOACG had more RCD and drugs per prescription than the noDOACG; routine laboratory monitoring was insufficient. What's known: Platelet aggregation inhibitors (low‐dose) are recommended for secondary prevention of cardiovascular events in patients suffering from symptomatic atherosclerosis. The main risk of this treatment is bleeding. What's new: A prescription for platelet aggregation inhibitors was found in 34% of geriatric inpatients in this prospective study. Compliance to guidelines was better for symptomatic peripheral artery disease than for primary prevention in accordance with recent publications. Geriatric comorbidities had no impact on the prescription of platelet aggregation inhibitors. Underuse of platelet aggregation inhibitors was observed in 11.3% of cases and overuse in 13.7% of cases.